Transição progressiva dos modelos explicativos de estudantes do nível médio sobre forças intermoleculares - Miranda, Ana Carolina Gomes (2018)
The research focus was the teaching and learning process of intermolecular forces at the middle level and the main objectives were to make a diagnosis about the approaches of this content, through a bibliographical research in published articles in the area of education, as well as to investigate the conceptual evolution, that is, if the explanatory models of students of the first series of high school on intermolecular forces form sequences of progressive transition, from the development of a didactic sequence. To reach the proposed objectives, this research was divided into two stages. In the first stage, a survey was carried out in national and international journals in the area of Teaching of Chemistry and Sciences between 1991 and 2015. The research was developed in four stages: 1) Selection of national and international journals for study; 2) Data collection by means of the collection of articles that approach the theme; 3) Screening from the full reading of the articles found and exclusion from those that do not deal with the topic; 4) Analysis of the articles, which was based on the following criteria: Characterization, Methodological Aspects, Theoretical Basis and Results. A total of 51 articles were identified in 11 journals and the results show: a predominance of international papers, and the increase in scientific production on the subject has intensified in the last ten years, while in Brazil this tendency has been observed in the last five years ; most of the articles are of an empirical nature, with a qualitative approach and prioritize Higher Education; the constructivist theory was the theoretical basis most used by the authors of the evaluated articles; the most recurrent alternative conceptions were the confusion between intermolecular forces and chemical bonds, and the difficulty of interpreting the properties of substances by intermolecular forces; a diversity of proposals for the content approach at different levels of education; the importance of establishing relationships between levels of representation of the subject for the understanding of the subject under study. Therefore, knowing the misunderstandings presented by students is the starting point for teachers and researchers develop didactic-pedagogical strategies that contribute to the conceptual evolution of this topic. The second stage, related to the investigation of the conceptual evolution on the content of intermolecular forces, occurred through the development of a didactic sequence developed for 52 students from two classes of the first grade of high school. Based on the perspective of Lakatos, we try to verify if the explanatory models of the subjects form progressive transition sequences, similar to what Lakatos, in the History of Science, refers to the problematic that increases the explanatory / heuristic power of the model. The evolution of the models, which usually consists of progressive transitions, is related to the understanding of the intermolecular forces content and the ability to move between levels of matter representation in three dimensions (intermolecular forces, London and dipole-dipole forces and hydrogen bonding). The follow-up of students' ideas throughout the study of the content of intermolecular forces revealed that in all dimensions there was a significant percentage of students who were able to progress during the research. In general, it is possible to affirm that the activities developed in didactic units contributed significantly to the progressive transition of the explanatory models of the majority of the participating students. In addition, the approach of the content of intermolecular forces in the didactic units enabled the students to interpret the phenomena under study, through the levels of representation of matter.